A Mindset for success - Swainston, Tony (Wales Crown House, 2017)
"A Mindset for Success: In Your Classroom and School" by Tony Swainston, published in 2017, explores how educators can cultivate a growth mindset within educational settings. Swainston emphasizes the importance of fostering grit, resilience, determination, and perseverance in students to enhance their academic and personal development. The book offers practical strategies for teachers and school leaders to implement mindset-focused approaches that encourage self-belief and a positive attitude toward learning.